ANALYSIS OF POLYMORPHISM OF THE GENES OF THE PHASE II OF XENOBIOTICS BIOTRANSFORMATION (GSTM1, GSTT1) IN THE SHORIANS AND ALIEN POPULATION OF THE KEMEROVO REGION: THE PROBLEM OF THE DIFFERENCES IN MORTALITY RATE FROM MALIGNANT NEOPLASMS - Лузина, Фаина Анисимовна; Дорошилова, Анастасия Викторовна; Смирнов, Владимир Юрьевич; Казицкая, Анастасия Сергеевна; Гуляева, Ольга Николаевна; Ядыкина, Татьяна Константиновна; Колбаско, Анатолий Владимирович (Medicine in Kuzbass, 2017)
Subject. Polymorphism of the genes of xenobiotics biotransformation GSTM1, GSTT1 (probable markers of cancer risk) in the Shorians and Europeoid population of the Kemerovo Region; mortality rates from malignant neoplasms (MNP) in the Shorians and the entire population in Novokuznetsk for the period from 1970 to 1999. Objective. To study the peculiarities of the distribution of the gene polymorphism of xenobiotics biotransformation (GSTM1, GSTT1) in the indigenous and alien population of the Kemerovo Region. To analyze ethno-genetic aspects of mortality rate from malignant neoplasms (on the example of Novokuznetsk). Materials and methods. The adult indigenous and alien population of Gornaya Shoria and Novokuznetsk of the Kemerovo Region was examined. DNA samples were selected from the venous blood by the phenol-chloroform extraction method. The deletion polymorphism of the GSTM1 and GSTT1 genes was studied by PCR method in real-time using LLC «SibDNA» reagent kit. We used data on mortality rates from MNP among the Shorians obtained from the archives of the recording of the acts of civil status in Novokuznetsk. Main results. The indigenous Shorians are dominated by the frequencies of the non-mutant variants of the genes of xenobiotics biotransformation: GSTM1 (+) is 0.768, GSTT1 (+) is 0.743; the frequency of «null» functionally weakened genotypes and their combinations compared with the Europeoid population is reduced. In the structure of the classes of death causes in the Shorians in the 90th years neoplasms are at the fourth ranked place (6.3 %), for the entire population of Novokuznetsk they are at the third one (11.7 %). Conclusions. The reduced frequency of the deletion variants of the genes of xenobiotics biotransformation (GSTM1, GSTT1) in the Shorians allows predicting the risk of disease incidence and mortality rates from oncologic pathology at the population level. Under the same ecological conditions of the urban environment mortality rates from MNP among the Shorians occupy a lower rank in the structure of the main classes of death causes in the comparison with the population of Novokuznetsk.